And in our hearts take up thy rest : the trinitarian pneumatology of Frederick Crowe, SJ - Eades, Michael, 1981- (Lonergan studies., 2019)
"In his seminary classes and his writings, Frederick Crowe, SJ (1915-2012) sought to understand anew the eternal identity of the Holy Spirit and the Spirit's role in the Church's life. Despite Crowe's fame as a professor of Trinitarian theology and his groundbreaking work on Thomas Aquinas' doctrine of complacent love as an analogy for the Holy Spirit's eternal procession, no book has ever been published on this influential Canadian Jesuit, who set up centres around the world for the study of the thought of Bernard Lonergan, SJ (1904-84). Drawing on Crowe's published works and archival material, Eades emphasizes how Crowe's Trinitarian pneumatology modestly and creatively extended Lonergan's theology of the Holy Spirit. Making use of Crowe's own historical methodology, Eades looks for the emergence of new and significant questions about the Holy Spirit in Crowe's works."--